Post-ball-milling-assisted solid-state synthesis of Bi4O4SeCl2: A low thermal conductivity material - Nattharika Theekhasuk; Nuttakrit Somdock; Athorn Vora–ud; Iyarat Ounrit; Pichet Limsuwan; Komsilp Kotmool; Rachsak Sakdanuphab; Aparporn Sakulkalavek (Results in Physics, 2025)
• Scalable synthesis of Bi 4 O 4 SeCl 2 via cost-effective ball-milling method. • Enhanced phase purity of Bi 4 O 4 SeCl 2 after 30 min of ball milling. • Electrical conductivity increased to 2.26 S/cm with optimized microstructure. • Achieved low thermal conductivity of 0.35 W/m·K for thermoelectric applications. • Experimental results align with DFT calculations, confirming structural evolution. This study investigates the synthesis of Bi 4 O 4 SeCl 2 through a cost-effective ball-milling-assisted solid-state reaction method. The as-grown samples predominantly consisted of the Bi 12 O 15 Cl 6 phase, with minor contributions from BiOCl and Bi 4 O 4 SeCl 2 . A systematic post-ball-milling process was applied to enhance the formation of the Bi 4 O 4 SeCl 2 phase. Prolonged milling time led to the progressive dominance of the Bi 4 O 4 SeCl 2 phase, resulting in significant improvements in electrical conductivity and reductions in thermal conductivity. After 30 min of milling, the carrier concentration increased notably from −2.23 × 10 16 cm −3 (as-grown) to −1.01 × 10 18 cm −3 , while electrical conductivity rose from 0.14 S/cm (as-grown) to 2.26 S/cm. Simultaneously, thermal conductivity decreased from 0.65 W m −1 K −1 (as-grown) to 0.35 W m −1 K −1 . These findings demonstrate that post-ball-milling is a scalable and economical method for synthesizing Bi 4 O 4 SeCl 2 with low thermal conductivity, highlighting its potential as a promising material for thermal barrier coatings and thermoelectric applications.
Keywords: Advanced Thermoelectric Materials and Devices; Advanced Condensed Matter Physics; Magnetic and transport properties of perovskites and related materials